Indonesia Perspective Related To Investor-Dispute Mechanism Draft Agreement of Regional Comprehensive Economic Partnership - Mutiara, Upik; Hasibuan, Rahmad Ramadhan; Candanni​Lupita Risma (International Journal of Global Community, 2020)
Regional Comprehensive Economic Partnership (RCEP) is a form of trade agreement between 10 ASEAN Member Countries and 6 ASEAN FTA partner countries which are started in 2011 with the aim of forming modern, interrelated and mutually beneficial economic partnerships between ASEAN member countries and ASEAN partner countries. The agreement which is still under negotiation between the participating countries is especially regulate the investor-state dispute settlement mechanisms which is being written under the Article XX concerning the State-Investor Dispute Settlement. Settlement of investment disputes through the Investor-State Settlement Settlement (ISDS) that still discussed in the draft Regional Comprehensive Economic Partnership (RCEP) multilateral partnership agreement currently being one of the debatable issues. This article will focus onthetheInvestor-StateDisputeSettlement(ISDS) mechanism and how its prospect of implementation in the International Comprehensive Economic Partnership agreement is within the framework of the general principles of International Trade Law by lookingatitfromanIndonesian perspective.